Digital Transformation and Change Management: An Analysis of the Impact of Artificial Intelligence and Big Data Implementation on Organizational Performance (Maneggio, 2025)
Digital transformation through the application of artificial intelligence (AI) and big data has become a key strategy in improving organizational performance in various sectors. The implementation of these technologies enables increased operational efficiency, accelerated decision-making, and innovation in services and products. However, on the other hand, organizations face various challenges, including technology infrastructure readiness, employee resistance to change, and data security risks. Therefore, an effective change management strategy is needed to ensure the successful implementation of AI and big data in supporting digital transformation. This research uses a qualitative approach with case study method and literature review. Case studies were conducted on organizations that have implemented AI and big data to analyze their impact on operational performance and business strategy. Data was collected through in-depth interviews with key stakeholders, observation of work processes, and analysis of organizational documents. In addition, a literature review was used to identify findings from previous research on the enablers and barriers of digital technology implementation.  The results show that the implementation of AI and big data has a positive impact on organizational performance, especially in improving efficiency, decision-making accuracy, and innovation. However, successful implementation is strongly influenced by the organization's readiness to face technical and cultural challenges. Organizations that have visionary leadership, effective change management strategies, and training programs for employees tend to be more successful in adopting digital technologies.